Improved prognosis of young patients with breast cancer undergoing breast‐conserving surgery. Issue 13 (9th August 2017) - Botteri, E.; Veronesi, P.; Vila, J.; Rotmensz, N.; Galimberti, V.; Thomazini, M. V.; Viale, G.; Orecchia, R.; Goldhirsch, A.; Gentilini, O.
Abstract : Background: The aim of the present study was to evaluate how breast cancer prognosis has evolved over time in young women treated with breast‐conserving surgery (BCS). Methods: Data from patients younger than 40 years who had BCS and whole‐breast radiotherapy in a single cancer centre between 1997 and 2010 were analysed. The patients were followed until 2016. Endpoints were local recurrence, any breast cancer‐related event and death from any cause. Results: A total of 1331 patients were included in the study. After a median follow‐up of 9·3 years, 114 local recurrences, 289 breast cancer‐related events and 138 deaths had occurred. Women were divided into three groups of similar size based on tertiles of the date of diagnosis: 1997–2002 (524 patients), 2003–2005 (350) and 2006–2010 (457). The risk of local recurrence was 1·42 per 100 person‐years in women diagnosed in the first interval, 0·85 per 100 person‐years in the second and 0·48 per 100 person‐years in the third ( P for trend = 0·028). The respective values were 3·01, 2·52 and 2·07 per 100 person‐years for any breast cancer‐related event ( P = 0·004), and 1·59, 1·22 and 0·64 per 100 person‐years for death ( P = 0·003). Each passing year was associated with a decreasing risk of local recurrence (hazard ratio (HR) 0·93, 95 per cent c.i. 0·87 to 1·00), any breast cancer‐related event (HR 0·94, 0·91 to 0·98) and death (HR 0·89, 0·83 to 0·94). A major improvement in prognosis was observed after 2005, when the classification of breast cancer molecular subtypes and use of trastuzumab were implemented in routine clinical practice. Conclusion: In the past two decades, both local control and overall prognosis have improved significantly in young women (aged less than 40 years) with breast cancer who undergo BCS. Abstract : Molecular subtype matters most